Investigation of linearity between mechanical properties of wood using graphical method - Mohd Jamil Abdul Wahab; Mohd Zamin Jumaat (Universiti Kebangsaan Malaysia, 2014)
Some basic requirements are set for small clear specimen data to incorporate Malaysian timbers into equivalent European timber strength classes. In general, the correlation between structural and small clear specimen test results must be established for every timber group regardless of origin. This paper introduces a sort-plot technique for analysing the correlation of some mechanical properties of timber in selecting appropriate parametric model. Bending test was conducted on mixed species hardwoods for the determination of strength and stiffness values of both structural and small size specimens. The results showed that the sort-plot diagrams demonstrate an obvious linearity pattern between timber properties despite having poor regression values. The technique verified that properties of timber in structural and small size specimens correlated linearly.